Trajectories of religion in Africa: essays in honour of John S. Pobee - Omenyo, Cephas Narh; Amanze, James N. (Studies in world christianity and interreligious relations, 2014)
The book, in the main, discusses issues relating to mission, ecumenism, and theological education and is presented in four sections. The first segment discusses works on ecumenical and theological education and assesses the relevance of the World Council of Churches. Other issues discussed in this segment relate to the interrelationships that exist between academic theology, ecumenism, and Christianity. The World Missionary Conference held in Edinburgh in 1910, which set the agenda for world-wide mission in a promising manner in the 1920s, is also assessed in this section of the work. 0The second segment, which covers Religion and Public Space, discusses works that examine the relationships between religion and power, religion and development, religion and traditional religious beliefs, and religion and practices in Africa. The third segment of the book treats Religion and Cultural Practices in African and how all these work out in couching out an African theology and African Christianity. Some of the issues discussed in this section related to African traditional philosophy, spiritism, and the interrelationships that exist between African Christianity and African Traditional Religion.0The last segment of the book discusses the issue of African biblical hermeneutics and specifically looks at contemporary hermeneutical approaches to biblical interpretations in Africa
Keywords: World Council of Churches -- History; Africa -- Religion -- 20th century; Aufsatzsammlung; Festschrift; Religion; Afrika